Endangered Voices: Nigerian Journalists' Safety amid the COVID-19 Pandemic - Alade, Moyosore (Springer, 2022)
This chapter examines the difficult conditions Nigerian journalists faced while reporting during the COVID-19 pandemic, focusing on the threats and dangers faced by Nigerian broadcast journalists and its implication for journalism practice amid a pandemic. Using a qualitative approach, we conducted nine in-depth interviews (online) with broadcast journalists in 2020 and employed thematic analysis to address the study’s findings. The study found that the safety threats encountered by journalists during the COVID-19 outbreak include the risk of contracting the virus, financial insecurity, and emotional trauma, among others. To combat these safety threats, journalists were responsible for their safety; hence, they ensured adherence to safety protocols with little or no support from the media houses they worked for. The implication of these safety threats to journalism practice includes reduced work output, reduced dissemination of factual reports, low-quality stories, and the lack of in-depth and investigative news reports during the COVID-19 pandemic in Nigeria.
Keywords: Journalists' Safety; Mental Health; COVID-19; Nigeria